Efficacy and safety profile of long‐term exposure to lenalidomide in patients with recurrent multiple myeloma. Issue 20 (6th August 2013) - Fouquet, Guillemette; Tardy, Stéphanie; Demarquette, Hélène; Bonnet, Sarah; Gay, Julie; Debarri, Houria; Herbaux, Charles; Guidez, Stéphanie; Michel, Jessica; Perrot, Aurore; Serrier, Caroline; Miljkovic, Darko; et al.
Abstract : BACKGROUND: Lenalidomide in combination with dexamethasone (Len/Dex) is indicated for patients with recurrent/refractory multiple myeloma (RRMM) who were treated with 1 prior therapy until evidence of disease progression. The objective of the current study was to determine the efficacy and safety profile of long‐term exposure to Len/Dex. METHODS: A total of 50 patients with RRMM who were treated with long‐term Len for ≥ 2 years from 2 Intergroupe Francophone du Myélome (IFM) centers (Lille and Nancy) were included in the current study. RESULTS: The median age of the patients was 58 years, with 30% of the patients aged > 65 years, 49% having an International Staging System stage of 2 and 3, 12% having severe renal insufficiency, and 8% demonstrating an adverse result on fluorescence in situ hybridization. Approximately 56% of the patients received treatment with Len/Dex for ≥ 3 years. The median duration of treatment with Len/Dex was 3 years (range, 2 years‐7 years). The response rates for partial response or better and very good partial response or better for the overall cohort were 96% and 74%, respectively, which is similar to patients exposed to Len for ≥ 3 years. With a median follow‐up of 4 years, 19 (38%) patients had stopped treatment with Len/Dex. The time to disease progression rate at 37 months was 78% and 91%, respectively, in patients exposed to Len for 2 years to < 3 years and for ≥ 3 years ( P  = 025). The safety profile was manageable, similar to that of Len when administered for a shorter period of time; 16% of patients had grade 3 to 4 neutropenia, 6% had thrombopenia, 6% had anemia, and 20% experienced thromboembolic events, all of venous type. The annual incidence rate of second primary malignancy was 1.96% in the current series. CONCLUSIONS: The results of the current study confirmed that the Len/Dex combination is feasible for long‐term use in patients with RRMM, with a significant benefit noted in terms of time to disease progression for prolonged treatment with Len/Dex. Cancer 2013;119:3680–3686 . © 2013 American Cancer Society . Abstract : The objective of the current study was to determine the efficacy and safety profile of long‐term exposure (≥ 2 years) to the combination of lenalidomide and dexamethasone in 50 patients with recurrent/refractory multiple myeloma (RRMM). The authors report an overall response rate of 96%, which is higher than expected, but that translated into a prolonged time to disease progression of 78% at 37 months, especially in patients exposed to lenalidomide for ≥ 3 years. The authors believe the results of the current study confirm that treatment with lenalidomide in combination with dexamethasone is feasible in the long‐term treatment of patients with RRMM. The safety profile of long‐term exposure to lenalidomide appears to be manageable, with a significant benefit in terms of time to disease progression noted in these patients.